Kekuatan Hukum Perjanjian Pengikatan Jual Beli Perumahan yang Tidak Terlaksana Sebagaimana Mestinya - Kasran Harefa; Busyra Azheri; Hengki Andora (UNES Law Review, 2023)
The legal force against the PPJB housing that is done by the P.T.Mutiara Peace made not in front of a notary in the form of a standard contract is weak and does not have a perfect legal force as the authentic act made in the presence of the notary. Such an agreement shall remain in force in that it is not contrary to the provisions of the law, the law and the common order. When the property is in the court of justice and because of its nature under the hand, then the proof is relative, that is, when the property has been admitted by the parties to its existence, the PPJB has the full legal force of proof, while for the party that does not admitt it then the power of evidence is handed over to the judge's consideration. And for them the parties of the Peace Mutiara with its buyer who perform PPJB in the presence of a notary in the form of an authentic act then the legal force is very binding and the value of the proof is perfect before the court. The position of PPJB in the sale of housing transactions between PT.Mutiara Peace with its buyer: First, that is made not in the presence of a notary in the form of a standard contract is already an agreement but its position is a preliminary agreement under the hand or called as the Preliminary Agreement for Sale of Sale. Second, for those parties that make the PPGB before the notary then the position is as an act whose nature is authentic in accordance with Article 1868 of the KUHPerdata or which is referred to as a contract of binding sale of sale.